Determination of the optimal target level of proteinuria in the management of patients with glomerular diseases by using different definitions of proteinuria. Issue 44 (November 2017) - Kee, Youn Kyung; Yoon, Chan-Yun; Kim, Seung Jun; Moon, Sung Jin; Kim, Chan Ho; Park, Jung Tak; Lim, Beom Jin; Chang, Tae Ik; Kang, Ea Wha; Kie, Jeong Hae; Yoo, Tae-Hyun; Jeong, Hyun Joo; et al.
Abstract : Abstract: Proteinuria is a major determinant of adverse renal outcome, and its reduction slows renal progression in glomerular diseases. However, the optimal target of proteinuria in glomerular diseases is unclear, and discrepancies in the definition of proteinuria produce ambiguous findings. Here we investigated the optimal target of proteinuria by using different definitions of proteinuria. We analyzed 574 IgA nephropathy (IgAN), 175 membranous nephropathy (MGN), and 177 focal segmental glomerulosclerosis (FSGS) cases from 3 Korean kidney centers. We evaluated the impact of proteinuria on renal outcome with 2 definitions: time-average proteinuria (TAP) and time-varying proteinuria (TVP). The endpoint was renal progression, defined as a 50% decline in glomerular filtration rate or end-stage renal disease. During a median follow-up of 57.3 months, the primary outcome occurred in 54 patients with IgAN, 26 with MGN, and 30 with FSGS. Multivariate Cox regression using TAP indicated that there was a linear association between proteinuria and risk of renal progression in IgAN. However, moderate proteinuria was not associated with an increased risk of renal progression in MGN and FSGS. In contrast, the analysis by TVP showed that the risk significantly increased in proportion to proteinuria during follow-up in all 3 diseases. Our findings suggest that TVP-based model can delineate association between proteinuria and risk of renal progression better than TAP-based model, considering that TVP reflects the dynamic change of proteinuria over time. Thus, proteinuria reduction to the lowest possible level is required to improve renal outcomes in patients with glomerular diseases. Abstract : Supplemental Digital Content is available in the text